Green Hospital Implementation in Dr. Cipto Mangunkusumo National Central Public Hospital - Nadiva Dzikriyati; Mursid Raharjo; Nurjazuli Nurjazuli; Baji Subagyo; Jamal Hisham Hashim (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2024)
Every day, hospitals carry out various health services and administrative activities constantly, so therefore hospitals are expected to reduce negative impacts on the environment by creating green hospitals. Green hospitals are hospitals that are designed, built, renovated, operated, and maintained by considering health and environmental development principles. This research used qualitative and quantitative methods. The qualitative method used is a case study method in the form of in-depth exploration from various perspectives related to the uniqueness of the green hospital system based on evidence obtained at the research location.  The quantitative method was carried out using a descriptive method in the form of simple statistics to describe the extent of green hospital achievements at Cipto Mangunkusumo General Hospital. The types of data collected are primary data from observation and in-depth interviews and secondary data from document review results. Implementation of green hospital in RSUPN Dr. Cipto Mangunkusumo, from 93 indicators 84,9% or 79 indicators are accomplished in RSUPN Dr. Cipto Mangunkusumo. The indicators with the most presentation are location and landscape, hopitals’ structure, Water efficiency, food processing, and air quality with 100% percentage. And the indicator with the least presentation are energy efficiency with 64,3% percentage.